Handbook of twentieth-century literatures of India - Natarajan, Nalini; Nelson, Emmanuel S. (Emmanuel Sampath) 1954- (Westport, Connecticut Greenwood Press, 1996)
Surveys the major regional literatures of contemporary India in the context of the country's diversity and heterogeneity. Focuses on literatures written in languages other than English, rather than the more commonly studied English-language postcolonial works.
Introduction : regional literatures of India---paradigms and contexts -- Twentieth-century Assamese literature -- Twentieth-century Bengali literature -- Twentieth-century Indian literature in English -- Twentieth-century Gujarati literature -- Twentieth-century Hindi literature -- Twentieth-century Kannada literature -- Twentieth-century Malayalam literature -- Twentieth-century Marathi literature -- Twentieth-century Panjabi literature -- Twentieth-century Tamil literature -- Twentieth-century Telugu literature -- Twentieth-century Urdu literature -- Dalit literature in Marathi -- Parsi literature in English -- Sanskrit poetics -- Perspectives on Bengali film and literature -- Selected general critical bibliography.
Keywords: Indic literature -- 20th century -- History and criticism -- Handbooks, manuals, etc; Indic literature -- 20th century -- History and criticism; Indic literature (English) -- History and criticism -- Handbooks, manuals, etc; Electronic books; India -- Intellectual life -- 20th century